Autism Characteristics and Self-Reported Health in Older Adulthood. (19th July 2021) - Lodi-Smith, Jennifer; Rodgers, Jonathan D; Kozlowski, Karl; Khan, Sarah; Marquez Luna, Valeria; Long, Caleb J; Donnelly, James P; Lopata, Christopher; Thomeer, Marcus L
Abstract: Objectives: The present research used a continuous measurement approach to extend the evidence that autism is associated with significant struggles in physical health as well as mental health and psychological well-being. Methods: The relationship of autism characteristics to physical health and psychological well-being was examined in 294 individuals ( M age = 70.51, SD age = 8.17, age range = 53–96). The sample is 57.4% female ( n = 166) and primarily White ( n = 270, 96.8%). The majority of the participants did not identify as having an autism diagnosis ( n = 284, 96.6%). Participants completed the Autism-Spectrum Quotient Scale alongside self-report measures of physical health, mental health, and psychological well-being. Results: Autism characteristics correlated strongly with challenges in social engagement due to poor health ( r = 0.46), depression ( r = 0.39) and anxiety ( r = 0.47), limitations due to poor mental health ( r = 0.41), satisfaction with life ( r = −0.47), and psychological well-being ( r = −0.62). Discussion: These findings help shed light on the challenges experienced by individuals aging with elevated autism characteristics. The limitations of this study and prior work on this topic help identify important avenues for future research in this area.